Effect and mechanism of longkui yinxiao soup in treating psoriasis in mice - Zhu, Congcong; Chen, Ya; Tai, Zongguang; Pan, Huijun; Shen, Min; Chen, Zhongjian; Zhu, Quangang (Frontiers in Pharmacology, 2023)
Objective: Longkui Yinxiao Soup (LYS) is a traditional Chinese medicine formula used to treat psoriasis for decades. Although LYS showed promising efficacy in clinical practice, the regulatory mechanisms of LYS remain elusive. This study aimed to explore the underlying mechanisms of LYS in a psoriasis-like mouse model. Methods: LYS was quality controlled by determining the contents of imperatorin and rhoifolin using high-performance liquid chromatography. The imiquimod-induced psoriasis-like mouse model was used to study the therapeutic effect and mechanism of LYS. The histopathological skin changes were observed by hematoxylin and eosin staining; the infiltration of proliferating proteins, proliferating cell nuclear antigen (PCNA) and Ki67, in skin tissues were observed by immunohistochemical (IHC) analysis; and the inflammatory factors such as interleukin (IL)-6, tumor necrosis factor (TNF)-α, IL-23, and IL-17 in serum were detected using enzyme-linked immunosorbent assay. RNA sequencing and bioinformatic analysis were used to predict the mechanism of LYS against psoriasis. mRNA expressions of p38, extracellular regulated protein kinases (ERK), mitogen-activated protein kinase kinase 3 (MEK3), mitogen-activated protein kinase kinase 6 (MEK6), RAP1 GTPase activating protein (Rap1gap), and Rap1 were determined using real-time quantitative polymerase chain reaction. The expression levels of proteins related to Rap1–mitogen-activated protein kinase (MAPK) signaling pathways were measured by Western blotting. Results: A quality-control method for LYS was successfully established using imperatorin and rhoifolin as content determination indexes. LYS significantly ameliorated the psoriatic symptoms in mice. The serum levels of inflammatory cytokines such as IL-6, TNF-α, IL-23, and IL-17 were decreased, and the expression levels of Ki67 and PCNA in skin tissues were downregulated. Moreover, the inhibition of Rap1–MAPK signaling pathways by LYS was detected. Conclusions: This study confirmed the antipsoriatic activity of LYS in psoriasis-like mice. This might be due to the inhibition of inflammatory factor secretion, keratinocyte proliferation, and the Rap1–MAPK signal pathway.